Rheological Study on ATBS-AM Copolymer-Surfactant System in High-Temperature and High-Salinity Environment - Muhammad Shahzad Kamal; Ibnelwaleed Ali Hussien; Abdullah Saad Sultan; Ming Han (Journal of Chemistry)
Experimental studies were conducted to evaluate the rheological properties of surfactant-polymer (SP) system. This SP system consists of a copolymer of acrylamide (AM) and acrylamido tertiary butyl sulfonate (ATBS) and sodium dodecyl sulphate (SDS) surfactant. Effects of surfactant concentration, temperature, polymer concentration, and salinity on rheological properties of SP system were investigated by means of oscillation and shear measurements. Comparison with classical partially hydrolyzed polyacrylamide (HPAM) was made. For the same temperature range, the viscosity drop for HPAM was about four times higher than the viscosity drop for ATBS-AM copolymer. In deionized water, viscosity of both polymers and SP systems was very high as compared to viscosity in saline water. Viscosity reduction of ATBS-AM copolymer was higher for salts having divalent cations. The SP system showed precipitation in presence of divalent cations. It worked well with monovalent cations even at relatively high salinities. The addition of 0.1% surfactant to the polymer resulted in a 60% decrease in the viscosity. Some interfacial rheological experiments were also carried out to investigate the behaviors on the interface between SP solutions and oil. Addition of 0.1% surfactant showed a 65% decrease in G′ at SP solution-oil interface. SP system consisting of ATBS-AM and SDS showed better performance at high temperature compared to HPAM-SDS system. Due to precipitation, the SP system should be restricted to environment having low divalent cations.